2018
DOI: 10.1080/1369183x.2018.1456748
|View full text |Cite
|
Sign up to set email alerts
|

International nurse migration from India and the Philippines: the challenge of meeting the sustainable development goals in training, orderly migration and healthcare worker retention

Abstract: International nurse migration from India and the Philippines: the challenge of meeting the sustainable development goals in training, orderly migration, and healthcare worker retention This paper examines nurse migration from India and the Philippines through the lens of the sustainable development goals (SDGs) 4.3 (access to training), 10.7 (orderly and responsible migration), and 3.c (retention of health workers). The international migration of health workers has increasingly featured on the agenda of global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 52 publications
1
33
0
Order By: Relevance
“…Inviting factors include the best salary, job improvement, better and more secure work environment, and appropriate lifestyle. Thompson et al, in 2019, showed that better care, higher salary, and fewer career risks in the developed countries are the influential reasons for emigration [12]. Thomas in 2006, also found that the dissatisfaction of the social attitude to nursing is another factor in desiring to emigrate for Indian nurses [13].…”
mentioning
confidence: 99%
“…Inviting factors include the best salary, job improvement, better and more secure work environment, and appropriate lifestyle. Thompson et al, in 2019, showed that better care, higher salary, and fewer career risks in the developed countries are the influential reasons for emigration [12]. Thomas in 2006, also found that the dissatisfaction of the social attitude to nursing is another factor in desiring to emigrate for Indian nurses [13].…”
mentioning
confidence: 99%
“…On the one hand, Filipino nurses' movement through provincial towns and small cities highlights issues that have long plagued the Philippines' health care system: the lack of funding for full-time positions within public hospitals, inequalities among rural and urban health institutions, and a for-profit education system that generated an oversupply of nursing graduates. Yet, as noted by Thompson and Walton-Roberts (2019), seemingly local problems are also constituted by issues that go beyond national borders. In the case of the Philippines, the nursing profession's status as a prime "export product" (Choy 2003;Guevarra 2010) led government officials to invest more on Filipino nurses' overseas employability than on health services in Philippine hospitals and clinics (Cabanda 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have criticized the framing of migration within the SDGs as territorially fixated (Hennebry et al 2018;Nijenhuis and Leung 2017). They have questioned the gendered character and experiences of migration as underrepresented (Gammage and Stevanovic 2018;Hennebry et al 2018;Holliday et al 2019) and describe how irregularity (Elias and Holliday 2018) and discrimination (Thompson and Walton-Roberts 2018) have been inadequately addressed by the global development goals. Adger et al (2019) fundamentally question the representation of migration in the SDGs, as still seeing migration as an exception rather than a normality.…”
Section: Migration and Sustainability Debatesmentioning
confidence: 99%